Customer experience dimensions and e-government success in United Arab Emirates - Al Hosani, Ahmed Ibrahim; Zainol, Zuraidah (Global Advances in Business Studies, 2022)
This systematic research study examined the connection between customer experience dimensions and e- government success in Abu Dhabi in United Arab Emirates (UAE). The organized study utilized a descriptive and cross-sectional survey research design with a positivism philosophy. A sample of 382 participants out of 108,825 target population was chosen employing a table developed by Morgan & Krejcie (1970). Facts were gathered utilizing a questionnaire, simple random sampling and examined applying Descriptive Statistics and Structural Equation Modeling using the Smart Partial Least Squares (SPLS) Version 3.3.3 software to test the hypotheses. The inquiry study findings came up with a significant correlation between customer experience dimensions (comfort, security and usability) and e- government success at significant level of 0.05. It was thus concluded that the customer experience dimensions significantly affect e- government success. The logical investigation study recommended that the UAE government should augment the budget for e-government successful implementation programs.